Aplicación de la fase de giro para el mejoramiento de la distancia en el lanzamiento del disco. - Mendoza Moreno, Víctor Alejandro (2022)
ABSTRACT: The present research project called "Application of the spin phase for the improvement of the distance in the discus throw", presents a descriptive cross-sectional study with the main objective of biomechanically evaluating the spin technique and the repercussion it has on the distance of the launch, based on this, to propose an exercise guide that allows developing in a better way the technical preparation of the discus throwing athletes. The study sample was divided into the stages of the investigation, a previous stage in which an observation sheet was made to 20 eighth grade students of Basic General Education of the Educational Unit "Carlos Cisneros" to determine the current situation of the planning of the training in this sports discipline and an experimental stage, in which a biomechanical study was carried out respectively. As instruments, an observation sheet designed to determine the actuality of the technical preparation in the throwing of the discus was used, the biomechanical analysis software kinovea 8.15, which allows us to capture video graphs allowing an evaluation of the different biomechanical parameters during the execution of the technical gesture under study and the methodology used was the breakdown of the sports technique by phases. The most relevant results were the obtaining of a structural model of the turning technique, as well as the distinction of the increase in its distance, which allowed carrying out the methodological guide of exercises for the application of the turning and the improvement of the distance in the turn discus throw. Keywords: Throw, disk, turn, distance